Is There a Future for Carbon Capture and Storage? - Ekeland, Anders; Kang, Rong; Kovárník, Jaroslav; Hamplová, Eva (Univerzita Hradec Králové, 2021)
The article discusses the political economy of CCS. The IPCC reports gives CCS a significant role in keeping global warming somewhere between 1.5 and 2 degrees Celsius, but still there is very few installations in operations and very few in the pipeline. This raises the question of why the diffusion of CCS has been slow and seem to slow down rather than speed up. First the paper discusses the question: When there is consensus the take-off of CCS depends on a high CO2 price, why is the price so low? Secondly discusses: What would happen if the CO2 price was 100 USD or higher? Would CCS then be the preferred way to reduce emissions or would other technologies be not only cheaper, but also faster and easier to implement? The paper concludes that the question the role of CCS in mitigating climate change also must be formulated as political problem, where the political/electoral effects of a high CO2 price plays a key role and needs to be taken much more explicitly into consideration than has been done so far. The paper uses primarily the fate of CCS in Norway as a case study of the political economy of CCS.
Je budoucnost v ukládání a skladování uhlíku?
Keywords: CCS; carbon capture and storage; carbon pricing; emission trading income distribution; just transition; CCS; ukládání a skladování uhlíku; oceňování uhlíku; distribuce příjmů z obchodování s emisemi; spravedlivé rozdělení